Phytomediated Biostimulation of the Autochthonous Bacterial Community for the Acceleration of the Depletion of Polycyclic Aromatic Hydrocarbons in Contaminated Sediments - Di Gregorio, Simona (Hindawi Publishing Corporation, 2014)
Polycyclic aromatic hydrocarbons (PAHs) are a large group of organic contaminants causing hazards to organisms including humans. The objective of the study was to validate the vegetation of dredged sediments with Phragmites australis as an exploitable biostimulation approach to accelerate the depletion of PAHs in nitrogen spiked sediments. Vegetation with Phragmites australis resulted in being an efficient biostimulation approach for the depletion of an aged PAHs contamination (229.67 ± 15.56 μg PAHs/g dry weight of sediment) in dredged sediments. Phragmites australis accelerated the oxidation of the PAHs by rhizodegradation. The phytobased approach resulted in 58.47% of PAHs depletion. The effects of the treatment have been analyzed in terms of both contaminant depletion and changes in relative abundance of the metabolically active Gram positive and Gram negative PAHs degraders. The metabolically active degraders were quantified both in the sediments and in the root endospheric microbial community. Quantitative real-time PCR reactions have been performed on the retrotranscribed transcripts encoding the Gram positive and Gram negative large α subunit (RHDα) of the aromatic ring hydroxylating dioxygenases. The Gram positive degraders resulted in being selectively favored by vegetation with Phragmites australis and mandatory for the depletion of the six ring condensed indeno[1,2,3-cd]pyrene and benzo[g,h,i]perylene.